Bonhoeffer, the Jewish People and Post-Holocaust Theology: Eight Perspectives; Eight Theses - Haynes, Stephen R. (Studies in Christian-Jewish Relations, 2011)
Over the years since his death, dozens of interpreters - scholars, novelists, dramatists, filmmakers and devotional writers- have offered a variety of perspectives on Bonhoeffer’s relationship to the Jewish people. This article describes eight distinct, though overlapping and largely compatible, perspectives on this question. It then identifies the author’s own view of this important relationship by presenting and developing eight theses. The author concludes that the desire to portray Bonhoeffer as a guide for post-Holocaust theological reflection is based less in Bonhoeffer’s theological achievements than in the compelling nature of his witness and the dire need for Christian heroes from the Nazi era.